New academia learning innovations in Universiti Malaya - Jariah Mohd. Jan; Siti Zaidah Zainuddin; Azlin Zaiti Zainal; Sheena Kaur; Roshidah Hassan (Penerbit Universiti Kebangsaan Malaysia, 2020)
Teaching and learning innovations in higher learning institutions have been radically changed over time to suit the once an agricultural nation to a more industrialised society. This change needs to be taken as the New Millennium Learners are influenced by advanced information and communication technologies. As we aim to achieve a shift towards more active learning through innovations, a variety of approaches are employed as we make use of digital and physical learning spaces. Blended learning that moves away from traditional classroom approaches with a more interactive learning is integrated in the teaching and learning process. The use of space beyond the conventional classroom setting enhances collaboration with peers and teachers from other countries. This paper intends to synthesise the innovative teaching and learning approaches in Universiti Malaya to accommodate the progressive change of the diverse academic community and industry requirements of our graduates. It aims to present an overview of the current academia learning innovations that have been taking place in the university that provide some form of engagement with technology. It also shows how instructors and students are supported by the various initiatives, approaches and collaborative efforts carried out by the university in keeping abreast with technological advancements. Finally several implications for teaching and learning in higher education are also discussed in this paper.